Review: chronic and persistent diarrhea with a focus in the returning traveler - Christopher A. Duplessis; Ramiro L. Gutierrez; Chad K. Porter (Tropical Diseases, Travel Medicine and Vaccines, 2017)
Abstract Background Travelers’ diarrhea is a common malady afflicting up to 50% of travelers after a 2-week travel period. An appreciable percentage of these cases will become persistent or chronic. We summarized the published literature reporting persistent/chronic diarrhea in travelers elucidating current understanding of disease incidence, etiology and regional variability. Methods We searched electronic databases (Medline, Embase, and Cochrane database of clinical trials) from 1990 to 2015 using the following terms: “chronic or persistent diarrh* and (returning) travel* or enteropathogen, GeoSentinel, and travel-associated infection. Included studies published in the English language on adult returning travelers (duration < 3-months) reporting denominator data. Point estimates and standard 95% confidence intervals were calculated for incidence using a random-effects model. Study incidence heterogeneity rates were assessed using x 2 heterogeneity statistics, graphically represented with Forest plots. Results We identified 19 studies meeting the inclusion criteria (all published after 1999). 18 studies reported upon the incidence of persistent/chronic diarrhea as a syndromic diagnosis in returning travelers; one study reported adequate denominator data from which to assess pathogen specific etiology. Giardiasis comprise an appreicaible percentage of infectious mediated persistent/chronic diarrhea in returning travelers. The overall estimate of persistent/chronic diarrhea incidence was 6% (0.05–0.07) in 321,454, travelers; with significant heterogeniety observed across regions. The total number of regional travelers, and point estimates for incidence (95% CI) for Latin American, African, and Asian travelers were [15816 (0.09 [0.07–0.11]), 42290 (0.06 [0.05–0.07]), and 27433 (0.07 [0.06–0.09])] respectively. We identified lower published rates of chronic diarrhea from Sub-Saharan Africa relative to [North Africa, South Central Asia, and Central America]. Persistent/chronic diarrhea ranked fourth as a ...